Encyclopedia of Analytical Chemistry 2000
DOI: 10.1002/9780470027318.a8101
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Chemical Analysis

Abstract: In recent years, archaeology has interacted more and more with the physical sciences. In particular, chemical analysis has been established as a significant contributor to science‐based archaeology. The principal applications include compositional analysis of natural and synthetic materials and residues to ascertain artifact manufacturing processes and use; chemical and isotopic studies of biological remains and identification of plant and animal residues to investigate ancient diet, nutrition, and resource us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 128 publications
0
91
0
6
Order By: Relevance
“…In a British context C 4 plants were not cultivated until the post-medieval period, so δ 13 C variations are dominantly used to distinguish between marine and terrestrial food sources (Pollard and Heron, 2008). Within the wider context of the Roman empire there is also the potential for millet and sorghum to contribute to the diet so that migrants to Roman…”
Section: Isotope Analysismentioning
confidence: 99%
“…In a British context C 4 plants were not cultivated until the post-medieval period, so δ 13 C variations are dominantly used to distinguish between marine and terrestrial food sources (Pollard and Heron, 2008). Within the wider context of the Roman empire there is also the potential for millet and sorghum to contribute to the diet so that migrants to Roman…”
Section: Isotope Analysismentioning
confidence: 99%
“…El estudio de los marcadores isotópicos se emplean en arqueología desde hace decenios, sustancialmente con el fi n de determinar el paleoclima, la dieta o la movilidad de las poblaciones antiguas (DeNiro 1987;Pollard y Heron 2008;Malainey 2010). En el caso del yacimiento de Dulantzi se han analizado los isótopos de nitrógeno y de carbono de 65 individuos para estudiar su dieta, y en 32 esqueletos los de estroncio para determinar si su origen era local o si, en cambio, se trataba de inmigrados 8 .…”
Section: Métodos Y Materialesunclassified
“…It has been suggested that this may be due to the origin of basaltic material from (with a few important exceptions such as the early Holocene Saksunarvatn Tephra) less explosive volcanism (Dugmore et al, 1995). Alternatively, it may be possible that basaltic shards have been affected by post-deposition dissolution (Pollard et al, 2003;Pollard and Heron, 2008). WolffBoenisch et al (2004) showed that rhyolitic glass has an expected lifetime of $10 times longer than basaltic glass at pH 4 and 258C.…”
Section: Basaltic Tephra Horizons In Distal Areasmentioning
confidence: 99%
“…from the eruptions of Katla in AD 1625, 1660 and 1755 (Thorarinsson, 1981). These basaltic eruptions, however, have not left any traces in the sedimentary records outside Iceland possibly due to low concentrations of tephra (Dugmore and Newton, 1998) or as a result of post-depositional dissolution which particularly affects basaltic glass (Pollard et al, 2003;Wolff-Boenisch et al, 2004;Pollard and Heron, 2008). Up until now, only two basaltic tephras from the last 1000 a -Veiðivö tn-1477 and Laki-1783 -have been traced in distal locations.…”
Section: Introductionmentioning
confidence: 99%